Factors Causing Students’ Disruptive Behavior in Learning English: A Case Study - Hardiani Ardin (Institut Parahikma Indonesia, 2020)
One of the most serious problems in effective teaching and learning processes at the secondary level is students' disruptive behavior. All stakeholders should have been giving more attention to students' disruptive behavior especially during learning processes. This study aimed to give a descriptive account of the factors causing students’ disruptive behavior in learning English based on the case study of a student who is categorized as the most disruptive student in learning English. This study applied descriptive qualitative research by using a purposive sampling technique. Two of the EFL teachers, a counselor, two of his classmates, and one of his family were interviewed for the data collection. The observation checklist and field notes were also used to show the student's disruptive behavior when learning English. The data analysis consisted of the data collection, data reduction, data display, and conclusion: drawing/verification. The findings showed that the factors causing the student’s disruptive behavior in learning English were (a) seeking attention, (b) classmate, (c) close friend, (d) learning environment, (e) family, and (f) social environment. It can be inferred that the most dominant cause of student’s disruptive behavior came from external factors.